Practice and scientificity in contemporary production applied to Art, Architecture and Design - Martínez-Osorio, Pedro; Guerrero Torrenegra, Alejandro; Castellanos Tuirán, Alexandra (Estoa. Journal of the Faculty of Architecture and Urbanism, 2026)
A reflection is proposed around the most representative aspects of the debate on scientific production in arts, architecture and design, towards the discussion for its legitimacy and demystification of the barriers about what is or is not valid in the production of scientific knowledge. Based on a bibliographic review, the favorable scenarios that allow the validation of all forms of knowledge are described as a contribution to the understanding and reflection of contemporary problems. The overview of research directed by project practice and aspects related to subjectivity and scientificity in creative disciplines is presented. The dynamic context of the contemporary world demands from different disciplines a greater concern for analyzing their methodologies and forms of knowledge production. The design disciplines, due to their great creative load, require a greater commitment to new ways of approaching knowledge towards innovation.